EFFECT OF WFH AND WORKLOAD ON EMPLOYEE PERFORMANCE THROUGH WORK RODUCTIVITY AS A MEDIATION VARIABLE (Study at PT NEO Pekanbaru) - Ayu Handayani Handayani; Raja Padil Padil; Haji Mustaqim Mustaqim (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
The purpose of this study is to empirically prove the effect of Work From Home and Workload on Employee Performance Moderated by Work Productivity. This research was conducted on employees of PT. Neo, Pekanbaru by using saturated sampling method with a total of 69 employees. This research method uses a quantitative approach using the SmartPLS version 3 software. The results of this study are work from home has an effect on work productivity, work from home has an effect on employee performance, workload has no significant effect on work productivity, workload has a significant effect on employee performance, work productivity can moderate the relationship between work from home and employee performance and Work productivity cannot moderate the relationship between workload and employee performance